2005
DOI: 10.1111/j.1523-1755.2005.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

A cute plasma ghrelin and leptin responses to oral feeding or intraperitoneal hypertonic glucose-based dialysate in patients with chronic renal failure

Abstract: Ghrelin secretion is partially refractory to the acute inhibitory effect of oral feeding in patients with CRF undergoing PD therapy. A 3.86% glucose-based PD exchange results in a significant decrease of plasma ghrelin levels. Plasma leptin levels are not acutely affected by oral feeding in patients with CRF or healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 61 publications
2
35
0
1
Order By: Relevance
“…We demonstrate that levels of DG but not AG increase with declining eGFR, and that ghrelin metabolism or secretion may be altered by uremia. AG response to feeding was blunted in CKD and absent in ESRD participants, as also reported by others (24,25). These results suggest that AG secretion is within the normal range and its conversion to DG is normal, but DG accumulates as its clearance is progressively decreased with declining eGFR.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…We demonstrate that levels of DG but not AG increase with declining eGFR, and that ghrelin metabolism or secretion may be altered by uremia. AG response to feeding was blunted in CKD and absent in ESRD participants, as also reported by others (24,25). These results suggest that AG secretion is within the normal range and its conversion to DG is normal, but DG accumulates as its clearance is progressively decreased with declining eGFR.…”
Section: Discussionsupporting
confidence: 68%
“…In our studies in CKD, the decrease in postprandial levels was blunted, but the ratio of DG/AG was maintained, and there was actually an increase in DG postprandially in dialysis patients. Others have reported that AG metabolism was altered in dialysis patients, but did not report data on DG (24,25). Our findings suggest that not only is DG increased as eGFR declines, but that abnormalities in the response of the ghrelin axis to feeding occur as CKD develops.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…However, it must be acknowledged that the effects of des-acyl ghrelin on food intake regulation still need to be better elucidated since the available evidence appears controversial [19, 20, 33]. Indeed, a recent paper by Perez-Fontan et al [34] showed a blunted response of both total and acylated ghrelin to oral intake in peritoneal dialysis patients. These data seem to suggest that in uremic patients ghrelin’s stimulatory and inhibitory pathways are disturbed, leading to increased levels of des-acyl-ghrelin promoting/maintaining reduced appetite and food intake.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of the assay was 1 µU/ml, and the normal value was <17 µU/ml. (2) Serum GLP-1 [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36] was quantified using a commercial enzyme immunoassay kit (DRG International, USA). The intra- and interassay coefficients of variation were <5 and <14%, respectively, and the sensitivity of the assay was 0.10 ng/ml.…”
Section: Methodsmentioning
confidence: 99%